The Impact of Za'atar Antioxidant Compounds on the Gut Microbiota and Gastrointestinal Disorders: Insights for Future Clinical Applications - Mohamad Khalil; Hala Abdallah; Danute Razuka-Ebela; Maria Calasso; Maria De Angelis; Piero Portincasa (MDPI AG, 2023)
Since the gut microbiota plays a pivotal role in host homeostasis and energy balance, changes in its composition can be associated with disease states through the promotion of immune-mediated inflammatory disorders and increasing intestinal permeability, ultimately leading to the impairment of intestinal barrier function. Za'atar is one of the most popular plant-based foods in the Eastern Mediterranean region. Za'atar is a mixture of different plant leaves, fruits, and seeds and contains hundreds of antioxidant compounds, especially polyphenols, and fiber, with pre-clinical and clinical evidence suggesting health-promoting effects in cardiovascular and metabolic disease. Za'atar compounds have also been studied from a gastrointestinal perspective, concerning both gut microbiota and gastrointestinal diseases. Antioxidants such as Za'atar polyphenols may provide beneficial effects in the complex interplay between the diet, gut microbiota, and intestinal permeability. To our knowledge, no studies have reported the effects of the whole Za'atar mixture, however, based on the pre-clinical studies published on components and single compounds found in Za'atar, we provide a clinical overview of the possible effects on the gastrointestinal tract, focusing mainly on carvacrol, rosmarinic acid, gallic acid, and other polyphenols. We also cover the potential clinical applications of Za'atar mixture as a possible nutraceutical in disorders involving the gastrointestinal tract.